1999
DOI: 10.2527/1999.77102832x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phosphorus on finishing steer performance, bone status, and carcass maturity.

Abstract: Yearling crossbred steers (n = 60; 386 kg) were individually fed in a completely randomized experimental design to determine their P requirement. Treatments were in a factorial arrangement with two levels of Ca (.35 or .70% of DM) and five concentrations of P (.14, .19, .24, .29, or .34% of DM). The finishing diet consisted of 34.5% dry-rolled corn, 22.5% brewers grits, 22.5% corn bran, 7.5% ground corncobs, 5% molasses, 3% fat, and 5% supplement. Supplemental P was provided as monosodium phosphate and Ca as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
1
31
1
11
Order By: Relevance
“…Using increasing levels of P in diets containing 0.30 or 0.70% calcium, Erickson et al (1999) found no interactions between Ca and P levels on performance as Ca:P ratios declined from 5:1 to 1:1. Performance was not affected with Ca:P ratios as low as 1:1 in the trials of Ricketts et al (1970).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using increasing levels of P in diets containing 0.30 or 0.70% calcium, Erickson et al (1999) found no interactions between Ca and P levels on performance as Ca:P ratios declined from 5:1 to 1:1. Performance was not affected with Ca:P ratios as low as 1:1 in the trials of Ricketts et al (1970).…”
Section: Resultsmentioning
confidence: 99%
“…Dietary calcium in excess of requirements has improved gain or feed efficiency in some trials (Huntington 1983;Brink et al 1984;Bock et al 1991). However, excess levels of limestone have reduced DMI and even gains in other trials (Russel et al 1980;Hironaka 1988;Erickson et al 1999), possibly through reduced OM digestion resulting from increased rumen fluid dilution rates (Goetsch and Owens 1985).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar experiment with yearling steers (BW = 385 kg), supplementation of P did not improve performance (Erickson et al, 1999). Dietary P fed to yearlings in that study ranged from 0.14 to 0.34% of diet DM, with individual intakes of 16 to 36 g/d equating to a range of 71 to 162% of NRC recommendations (Erickson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, P requirements are not well established for beef feedlot cattle weighing between 270 and 600 kg. Erickson et al (1999) evaluated P requirements of yearling steers (380 kg) with typical feedlot gains (> 1.5 kg/d) and concluded that the requirement 1690 matter intake and ADG did not change linearly (P > 0.86) or quadratically (P > 0.28) due to P treatment. Feed efficiency was not influenced (P > 0.30) by P treatment and averaged 0.169.…”
Section: Introductionmentioning
confidence: 99%
“…Erickson et al (1999) evaluated P requirements of yearling steers (380 kg) with typical feedlot gains of 1.5 kg d-I and concluded that the P requirement was ~0 . 1 4 % of diet DM, or 70% of the NRC (1996) recommendations.…”
Section: Phosphorus Requirements Of Beef Cattlementioning
confidence: 99%